Piecewise-deterministic Markov chain Monte Carlo - Vanetti, P (2019)
Recent interest in a class of Markov chain Monte Carlo schemes based on continuous-time piecewise-deterministic Markov processes has led to several new and promising algorithmic developments. Prominent examples include the zig-zag process and the bouncy particle sampler. We explore this class of algorithms, proposing extensions and drawing connections to existing literature.